2018
DOI: 10.5114/pjr.2018.81281
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted magnetic resonance imaging in the differentiation of benign and malignant pulmonary lesions

Abstract: PurposeTo evaluate the role of magnetic resonance (MRI) diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) measurement of solid and cystic pulmonary masses in differentiating benign from malignant lesions.Material and methodsThe study included 41 patients with pulmonary masses, who underwent conventional MRI and DWI (b value 0, 500, and 1000 s/mm²) examinations with 1.5-T MRI. The diffusion signal and the mean ADC values of the solid and cystic lesions were obtained. Statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…As regarding the signal intensity of the lesions, in our study, we found that SI of the lesions on diffusion sequences were significantly higher among malignant pulmonary lesions than benign pulmonary lesion Our result is comparable to Çakmak et al [4] and Alnaghy et al [13] which also found that the SI lesion was significantly higher among malignant pulmonary lesions than benign pulmonary lesion (231.80 ± 139.492) versus (107.10 ± 74.497) respectively with p value < 0.001. As comparing the signal intensity of the lesions to that of the spinal cord, in our study, the calculated LSR was higher among malignant pulmonary lesions than benign pulmonary lesions (1.6 ± 0.36 for malignant lesions and 1.18 ± 0.59 for benign lesions) with p value 0.006.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As regarding the signal intensity of the lesions, in our study, we found that SI of the lesions on diffusion sequences were significantly higher among malignant pulmonary lesions than benign pulmonary lesion Our result is comparable to Çakmak et al [4] and Alnaghy et al [13] which also found that the SI lesion was significantly higher among malignant pulmonary lesions than benign pulmonary lesion (231.80 ± 139.492) versus (107.10 ± 74.497) respectively with p value < 0.001. As comparing the signal intensity of the lesions to that of the spinal cord, in our study, the calculated LSR was higher among malignant pulmonary lesions than benign pulmonary lesions (1.6 ± 0.36 for malignant lesions and 1.18 ± 0.59 for benign lesions) with p value 0.006.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results are seen in ÇAKIR et al 2015 and Alnaghy et al 2018 studies. The ADCs of the benign lesions were significantly higher than those of malignant lesions (mean ADC was 2.02 × 10-3 mm2/s for malignant lesions, and 1.195 × 10-3 ± 0.3 mm2/s for benign lesions) [2,13].…”
Section: Discussionmentioning
confidence: 90%
“…When comparing the mean ADC value of various pathological lesions, there was a statistically significant difference (p-value >0.001) ADC values of benign and malignant lesions are in agreement with (Alnaghy et al, 2018) [4], who found that the mean ADC value of benign lesions was 1.7-0.72 mm2/s, while the mean ADC value of malignant lesions was 1.09-0.0.19, which was significantly lower than the benign lesions with a p-value of 0.01.…”
Section: Discussionsupporting
confidence: 86%
“…Granulomatous lesions show areas of necrosis and abscess which shows falsely lower ADC values. 27 However, these areas of necrosis were excluded from ROI during parametric imaging.…”
Section: Discussionmentioning
confidence: 99%